A nest for Celeste : a story about art, inspiration, and the meaning of home - Cole, Henry, 1955- (Katherine Tegen Books, 2010)
Celeste, a mouse longing for a real home, becomes a source of inspiration to teenaged Joseph, assistant to the artist and naturalist John James Audubon, at a New Orleans, Louisiana, plantation in 1821.